Comparative Assessment of Topical Platelet-Rich Plasma and Phenytoin for Diabetic Foot Ulcer Healing in a Rat Model - Khadiga T. Al-Thubhani; Doa’a A. Ibrahim; Mahmood Al-Hammadi (University of Science and Technology, Sana’a, Yemen, 2026)
Background: Diabetic foot ulcer (DFU) is a major complication of diabetes, associated with increasing rates of lower-limb amputation, morbidity, and mortality. Treating DFU remains a growing medical challenge, with many current approaches failing to achieve optimal outcomes. One approved clinical approach involves regenerative therapies, such as platelet-rich plasma (PRP). Another approach is drug repurposing, including the topical use of phenytoin. This study aimed to compare the wound-healing efficacy of 1% phenytoin cream with that of PRP gel in a rat model of DFU. Methods: This experimental study was conducted over 84 days using 20 adult male albino rats. Diabetes was induced by feeding the rats a high-fat diet for 28 days, followed by a single intraperitoneal injection of streptozotocin (STZ) at 40 mg/kg. After diabetes confirmation, diabetic neuropathy was assessed on day 42, and a wound was induced on the right hind paw of each rat on day 43 using a 6-mm biopsy punch. Wounds were treated to prevent infection for 14 days. On day 60, rats were randomly divided into two groups: diabetic wounds treated once daily with 1% phenytoin cream (DW Phen, n = 10) and diabetic wounds treated twice weekly with freshly prepared PRP gel (DW PRP, n = 10), from day 60 to day 84. Wounds were photographed on days 60, 64, 67, 70, 74, 77, 82, and 84, and wound area and contraction were recorded. On days 70, 77, and 84, two rats randomly selected from each group were sacrificed, and wound sections were obtained for histopathological assessment and immunohistochemistry (IHC) studies. Results: PRP gel and phenytoin cream showed comparable efficacy in terms of wound contraction, histopathological findings, and IHC results. Although the PRP gel showed greater wound contraction, the differences between the DW PRP and DW Phen groups were not statistically significant. Histologically, early wound sections in the DW Phen showed edema, extravasated red blood cells, and less collagen reconstruction, whereas the DW PRP group showed more advanced granulation tissue, neovascularization, and collagen deposition. In the middle and final stages, both treatments promoted tissue repair, re-epithelialization, fibroblast proliferation, collagen organization, and hair follicle formation, with PRP showing more advanced tissue reconstruction and rete ridge restoration. IHC staining confirmed effective vascularization in both groups. Conclusion: PRP achieves complete wound closure by day 84, whereas phenytoin shows near-complete closure, with no statistically significant difference. Wound healing is supported by enhanced tissue regeneration, re-epithelialization, and angiogenesis. PRP shows more advanced histological improvement than phenytoin. Future studies should develop standardized protocols for PRP application, with consideration of dosage form, route of administration, stability, and the molecular mechanisms underlying wound healing.